Diffusion and Adoption of Semidwarf Rice Cultivars As Parents in Asian Rice Breeding Programs - Hargrove, Thomas R. (Wiley, 1979)
The first widely grown semidwarf cultivars of rice (Oryza sativa L.) were ‘Taichung Native 1’ (TN1), released in 1956, and ‘IR8’, in 1967. To determine the impact of new semidwarf cultivars on the genetic diversity of the world's rice crop, the International Rice Research Institute (IRRI) traced the diffusion and adoption of improved rice cultivars as parents among national breeding programs at 14 agricultural research centers in seven Asian nations from 1965 to 1975.Sixty‐one percent of the 1965–67 crosses and 84% of the 1974–75 crosses involved at least one semidwarf parent. Crosses that involved a tall cultivar decreased. In 1965–67, 28% of the total gene pool was semidwarf and 40% tall. Ten years later, the percentage of semidwarfs almost doubled and that of talls dropped sharply. Apparently, breeders were increasingly crossing semidwarf parents to other semidwarfs.TN1 and IR8 were the most popular gene sources in 1965–67; each was used in about 20% of the crosses. Use of TN1 and IR8 dropped to only 1 to 3% by 1974–75, while use of other IRRI semidwarfs increased significantly. But the strongest trend was the growing use of locally developed semidwarfs — from 2% of the 1965–67 crosses to 49% in 1974–75. The genetic makeup of those local semidwarf parents was traced back two generations; 76% were progeny of IR8 or other IRRI rices.Breeders in India adopted TN1 and IR8 earlier, and more extensively, than breeders in the six other countries. By 1974–75, 75% of Indian crosses involved a local semidwarf. In the six other countries, IRRI remained the major source of semidwarf breeding material but breeders increasingly used local semidwarfs. The semidwarf indica rices largely replaced japonica, ponlai, and other races in the breeding programs.